Extracellular vesicles secreted by adenomyosis endometrial organoids contain miRNAs involved in embryo implantation and pregnancy. Issue 3 (March 2023) - Juárez-Barber, Elena; Segura-Benítez, Marina; Carbajo-García, María Cristina; Bas-Rivas, Alba; Faus, Amparo; Vidal, Carmen; Giles, Juan; Labarta, Elena; Pellicer, Antonio; Cervelló, Irene; Ferrero, Hortensia
HIGHLIGHTS: miRNA cargo of adenomyosis secretory phase EVs promote implantation failure. miRNA cargo of adenomyosis gestational phase EVs promote pregnancy disorders. Adenomyotic-miRNAs modulate mechanisms involved in adenomyosis-related infertility. Adenomyotic-miRNAs may be potential biomarkers of adenomyosis reproductive outcomes. Abstract: Research question: Do extracellular vesicles secreted by the endometrium of women with adenomyosis contain miRNAs involved in adenomyosis-related infertility? Design: A descriptive study using organoids from eutopic endometrium of women with adenomyosis ( n = 4) generated and differentiated to secretory and gestational phases, in which miRNA cargo from extracellular vesicles secreted by these differentiated organoids in each phase was analysed by next-generation sequencing. miRNAs in secretory-extracellular vesicles and gestational-extracellular vesicles were selected based on the counts per million. miRNAs target genes in each phase were obtained from miRNet and gene ontology was used for enrichment analysis. Results: miRNA sequencing identified 80 miRNAs in secretory-phase extracellular vesicles, including hsa-miR-21-5p, hsa-miR-24-3p, hsa-miR-26a-5p, hsa-miR-92a-3p, hsa-miR-92b-3p, hsa-miR-200c-3p and hsa-miR-423a-5p, related to adenomyosis pathogenesis and implantation failure. Further, 60 miRNAs were identified in gestational-phase extracellular vesicles, including hsa-miR-21-5p, hsa-miR-26a-5p, hsa-miR-30a-5p, hsa-miR-30c-5p, hsa-miR-222-3p and hsa-miR-423a-5p were associated with preeclampsia and miscarriage. Among the target genes of these miRNAs, PTEN, MDM4, PLAGL2 and CELF1, whose downregulation ( P = 0.0003, P < 0.0001, P = 0.0002 and P = 0.0003, respectively) contributes to adenomyosis pathogenesis, and impaired early embryo development, leading to implantation failure and miscarriage, are highlihghted. Further, functional enrichment analyses of the target genes revealed their involvement in cell differentiation, proliferation, apoptosis, cell cycle regulation and response to extracellular stimuli. Conclusions: Eutopic endometrium in secretory and gestational phase from women with adenomyosis releases extracellular vesicles containing miRNAs involved in adenomyosis progression, impaired embryo implantation and pregnancy complications. Graphical abstract: Image, graphical abstract